PENDIDIKAN ANAK USIA DINI BERBASIS PSIKOLOGI ISLAM - Devy Habibi Muhammad; Agustiarini Eka Deasari; Aries Dirgayunita (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2021)
The purpose of this study is to explain early childhood education based on Islamic psychology, a study approach to understanding children's psychology and behavior based on the concept of monotheism, through the integration of science and faith. Islamic psychology is a form of psychology that is based on the image of humans in Islam, which has uniqueness and patterns of human behavior as an expression of the experience of interaction with the environment and the spiritual world with the aim of improving mental health and the quality of religious life, and achieving happiness in the world and the hereafter. One of the efforts to rebuild human civilization and perfecting the concept of human behavior is to educate and understand the concept of education in Islam, as well as a refinement of a soul filled with faith based on the Al-Qur'an and Hadith. In Islamic education, it has laid the foundation of the Al-Qur'an regarding the goals of education and Islamic material that must be taught in Islamic education. learning will be delivered using a method that must be an interesting and important issue in Indonesia to achieve the expected goals of Islamic education. Based on that, it is very closely related to the task of Islamic psychology. Pure souls will easily accept and apply the existing Islamic education concept based on the Al-Qur'an and Sunnah of the Prophet Muhammad. These two pillars are the basic concepts of Islamic education.